Legislation - Malaysia, Government of (Journal of Malaysian and Comparative Law, 2019)
The following list of Act passed in Malaysia is a continuation of the list of Federal Acts contained in Vol. 10 Parts 1 & 2 (1983) J.M.C.L. 255-258.